1997
DOI: 10.1046/j.1365-2133.1997.18171898.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ulcerative stomatitis

Abstract: Chronic ulcerative stomatitis (CUS) has recently been described as a new disease entity characterized by chronic ulceration of oral mucosa which responds to treatment with hydroxychloroquine. It has a particular type of stratified epithelium-specific, antinuclear autoantibody as an immunological marker. Twelve cases have been reported in the literature. We present a 40-year-old woman with an 11-year history of chronic oral ulcerations. Other dermatological diseases, including oral lichen planus, pemphigus vulg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 7 publications
1
36
0
Order By: Relevance
“…None of the 10 patients had any significant skin lesions 17 The microscopic findings were generally nonspecific but demonstrated lichenoid features, such as ulceration, hydropic degeneration of basal layer cells and reduplication of the basement membrane, variation in epithelial thickness (with some lesions having a flat interface between the epithelium and connective tissue), saw-tooth rete ridges, and colloid bodies. The band-like infiltration of inflammatory cells varied in composition, with some infiltrates composed purely of lymphocytes and others having a mixture of lymphocytes and plasma cells.…”
Section: Resultsmentioning
confidence: 94%
“…None of the 10 patients had any significant skin lesions 17 The microscopic findings were generally nonspecific but demonstrated lichenoid features, such as ulceration, hydropic degeneration of basal layer cells and reduplication of the basement membrane, variation in epithelial thickness (with some lesions having a flat interface between the epithelium and connective tissue), saw-tooth rete ridges, and colloid bodies. The band-like infiltration of inflammatory cells varied in composition, with some infiltrates composed purely of lymphocytes and others having a mixture of lymphocytes and plasma cells.…”
Section: Resultsmentioning
confidence: 94%
“…Treatment is with potent topical steroids or hydroxychloroquine, the latter reportedly bringing about complete and long lasting remission. 13,40,61,62 …”
Section: Pemphigusmentioning
confidence: 99%
“…Other lesions may appear non‐specific: a few patients have shown an asymmetrical distribution and single‐site involvement. In nine cases, vesicles and Nikolsky's sign were observed (Beutner et al, ; Chorzelski et al, ; Ko et al, ; Reddy et al, ; Wörle et al, ).…”
Section: Reviewmentioning
confidence: 99%
“…To date, 72 cases have been reported (Alshagroud, Neiders, Kramer, & Suresh, ; Beutner et al, ; Chorzelski, Olszewska, Jarząbek‐Chorzelska, & Jablońska, ; Church & Schosser, ; Fourie, van Heerden, McEachen, & van Zyl, ; Islam et al, ; Jaremko et al, ; Kapińska‐Mrowiecka, Czubak‐Macugowska, Michcik, Chomik, & Wlodarkiewicz, ; Ko, Danciu, Fullen, & Chan, ; Lewis, Beutner, Rostami, & Chorzelski, ; Lorenzana, Rees, Glass, & Detweiler, ; Molenda & Kozlowski, ; Parodi & Cardo, ; Qari et al, ; Reddy, Fitzpatrick, Bhattacharyya, Cohen, & Islam, ; Solomon et al, ; Wörle et al, ). However, a literature review has indicated that its prevalence in the general population could be underestimated (Solomon, ).…”
Section: Introductionmentioning
confidence: 99%